Mendeskripsikan Testimoni sebagai Fenomenologi Sosial - Nugroho, Ibnu (Dekonstruksi, 2025)
This paper is a study entitled “Describing Testimony as Phenomenology of Social”. Testimony is described in various ways, even its existence is distinguished from each other. It is indicated that the testimony is formed from four connected elements, then, the testimony is distinguished between natural and formal. In this study, the thesis reveals that testimony is a social interaction that occurs through speech and the relationship of intersubjectivity, this is shown in the writing of Gerrit Jan Van Derr Heiden in The Voice of Misery. Dealing with the thesis, this study develops attractual interaction as the pioneer of testimony in social phenomenology. This attractual interaction is based on Georg Simmel’ idea on aesthetic sociology. The result of this study finds out that there is a relation of testimony within the scope of social phenomenology. The relation is obtained by representing the possibilities of social theory that has been discovered